Systems and processes for regulation of investigational medical devices in Uganda - Mpaata, Charles Norman; Matovu, Brian; Takuwa, Mercy; Kiwanuka, Noah; Lewis, Steff; Norrie, John; Ononge, Sam; Tuck, Sharon; Wolters, Maria; Demulliez, Marc; Ssekitoleko, Robert T. (Frontiers in Medical Technology, 2023)
Background In many parts of the world, medical devices and the processes of their development are tightly regulated. However, the current regulatory landscape in Uganda like other developing countries is weak and poorly defined, which creates significant barriers to innovation, clinical evaluation, and translation of medical devices. Aim To evaluate current knowledge, systems and infrastructure for medical devices regulation and innovation in Uganda. Methods A mixed methods study design using the methods triangulation strategy was employed in this study. Data of equal weight were collected sequentially. First, a digital structured questionnaire was sent out to innovators to establish individual knowledge and experience with medical device innovation and regulation. Then, a single focus group discussion involving both medical device innovators and regulators to collect data about the current regulatory practices for medical devices in Uganda. Univariate and bivariate analysis was done for the quantitative data to summarize results in graphs and tables. Qualitative data was analyzed using thematic analysis. Ethical review and approval were obtained from the Makerere University School of Biomedical Sciences, Research and Ethics Committee, and the Uganda National Council for Science and Technology. Results A total of 47 innovators responded to the questionnaire. 14 respondents were excluded since they were not medical device innovators. Majority (76%) of individuals had been innovators for more than a year, held a bachelor's degree with a background in Engineering and applied sciences, and worked in an academic research institute. 22 of the 33 medical device innovators had stopped working on their innovations and had stalled at the proof-of-concept stage. Insufficient funding, inadequate technical expertise and confusing regulatory landscape were major challenges to innovation. The two themes that emerged from the discussion were “developing standards for medical devices regulation” and “implementation of regulations in practical processes”. Legal limitations, lengthy processes, and low demand were identified as challenges to developing medical device regulations. Conclusions Efforts have been taken by government to create a pathway for medical device innovations to be translated to the market. More work needs to be done to coordinate efforts among stakeholders to build effective medical device regulations in Uganda.